COMPETING VIA CREATION OF DISTINCTIVE ORGANIZATIONAL COMPETENCES: "HOW TO DO IT" (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The purpose of this paper is to twofold: (1) to identify specific and generic organizational competences that compose three different types of competitive advantages – product leadership, customer intimacy and operational excellence – and (2) to identify processes and approaches by which identified organizational competences are developed. Using multi-case study approach, the main findings come into two tentative theory building conclusions. (1) Behind different ways of competing there there are only four distinct organizational competences – innovation competence, competence of managing business risks, operational competence and stakeholder influence competence. These four competences form three distinct ways of competing: competing via product leadership, competing via customer intimacy and competing via operational excellence. (2) All four organizational competences are composed of nine organizational processes and approaches: bonding, attracting, showcasing, specialization, capitalization, internationalization, specialization, quality control, cost monitoring, and shielding. However, due to the case study research design this paper provides limited generalizability and thus calls for validations via quantitative research approaches.Keywords: competitive advantage, value proposition, organizational competences, competence creation processes